Study on customer satisfaction towards after-sales service by Mercedes-Benz Malaysia / Norain Karim - Karim, Norain (Faculty of Business and Management, 2011)
These days all organizations are realizing the significant of customer-centered philosophies. One of the key challenges of them is how they manage service quality, which holds a great important to customer satisfaction. The purpose of this research was to gain a better understanding of the service quality dimensions in after-sales service department that affect customer satisfaction from customer perspectives. Based on a detailed literature review, a frame of references was developed. Five service quality dimensions were selected to be tasted in this research for after sales service department in Mercedes-Benz Malaysia and its relationship with customer in order to explore the relationship between service quality and customer satisfaction. This research has been answered by 100 respondents through questionnaire. Instead of it, the Statistical Package for the Social Science (SPSS) version 16.0 has been used to summarize the data. Based on this research, the result indicates level of five service quality dimension towards customer satisfaction is in high level. Besides that, results show there are significant relationship between four elements of service quality dimension with customer relationship which is service reliability, service responsiveness, service assurance and service empathy has strong relationship with customer satisfaction, means that these four elements have strong impact towards customer satisfaction. As a conclusion, the results of the findings that include the analysis of the demographic profile, general information on customer satisfaction and elements that most contribute in customer satisfaction. For recommendation of this study made based on several logical factors and the implications towards customer satisfaction.